Nischitha. j Asked a Question
June 15, 2020 12:45 pmpts 30 pts
i x-1 y-2 z-2=0 k 4 2 2 y-zi + (2z - x - 3)j + (x - 2y + 3)k = 0 y - z = 0 2z - x -3 = x - 2y + 3 X+3 = y = Z 2
  • 2 Answer(s)
  • 0 Likes
  • 3 Comments
  • Shares
  • Nischitha. j
    Thank u so much for the great reply
    Likes(0) Reply(0)
  • Arzoo thankyou
    See the attachment
    • cropped9152991868227714700.jpg
    Likes(0) Reply(0)
  • Priyadarshan Choursiya Best Answer
    compare both sides. see attachment
    • cropped4881305169032250982.jpg
    Likes(0) Reply(0)